2018
DOI: 10.3389/fpsyt.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Core Symptoms of Attention Deficit Hyperactivity Disorder and Both Binge and Restrictive Eating

Abstract: IntroductionIt is unclear whether core symptoms of attention deficit hyperactivity disorder (ADHD) relate to specific types of disordered eating and little is known about the mediating mechanisms. We investigated associations between core symptoms of ADHD and binge/disinhibited eating and restrictive eating behavior and assessed whether negative mood and/or deficits in awareness and reliance on internal hunger/satiety cues mediate these relationships.MethodsIn two independent studies, we used a dimensional app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 86 publications
6
63
1
3
Order By: Relevance
“…While studies have generally documented a relationship between greater ADHD symptoms and food approach behaviors, like food responsiveness, some studies have also found greater ADHD symptoms to be related to food avoidant behavior, such as food fussiness in children and restrictive eating in adults . Some of our findings also line up with these previous results in that we too found greater ADHD symptoms during preschool age were prospectively related to greater satiety responsiveness (a food avoidant behavior) from the preschool to early childhood period.…”
Section: Discussionsupporting
confidence: 89%
“…While studies have generally documented a relationship between greater ADHD symptoms and food approach behaviors, like food responsiveness, some studies have also found greater ADHD symptoms to be related to food avoidant behavior, such as food fussiness in children and restrictive eating in adults . Some of our findings also line up with these previous results in that we too found greater ADHD symptoms during preschool age were prospectively related to greater satiety responsiveness (a food avoidant behavior) from the preschool to early childhood period.…”
Section: Discussionsupporting
confidence: 89%
“…Our study and most earlier studies showed eating food in response to emotional distress correlated positively with ADHD in obese adults (Alfonsson et al., 2012, 2013; Pagoto et al., 2010). It is imaginable that to handle frustrations and negative affect resulting from the consequences of attention problems (eg poor work accomplishment) and/or impulsive reactions at the cost of planned objectives, people with ADHD could be into disordered eating (Kaisari et al., 2018). Notwithstanding, in overweight/obese children and adolescents Pauli‐Pott et al.…”
Section: Discussionmentioning
confidence: 99%
“…Binge eating was the most assessed eating pathology. Some studies have investigated direct and indirect pathways (Kaisari et al., 2018), mediators, and confounding factors between ADHD, comorbid disorders, and obesity. Some found the depression or binge eating as mediators of the relationship between ADHD and obesity (Cortese et al., 2013; de Zwaan, et al., 2011a, 2011b; Pagoto et al., 2009; Tong et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that impulsivity may be a core cognitive underpinning of BED (Kaisari, Dourish, Rotshtein, & Higgs, 2018). Impulsivity is a broad term referring to a disposition towards behaviours that are unduly hasty, risky, and that lead to undesirous outcomes (Grant & Chamberlain, 2014).…”
Section: Introductionmentioning
confidence: 99%